A historical guide to Walt Whitman - Reynolds, David S., 1948- (Historical guides to American authors., 2000)
Few authors are so well suited to historical study as Whitman, who is widely considered America's greatest poet. This Guide combines contemporary cultural studies and historical scholarship to illuminate Whitman's diverse contexts. The essays explore dimensions of Whitman's dynamic relationship to working-class politics, race and slavery, sexual mores, the visual arts, and the idea of democracy. The poet who emerges from this volume is no "solitary singer", distanced from his culture, but what he himself called "the age transfigured", fully enmeshed in his times and addressing issues that are still vital today.